6.8 Hepatic IGF1 DNA methylation and mRNA expression are influenced by gender but not by prenatal growth restriction in the young lamb. (9th June 2014) - Carr, DJ; Milne, JS; Aitken, RP; Wallace, JM
Abstract : Introduction: Early postnatal growth and body composition are variously influenced by fetal nutrient supply and gender. Thus relative to normal birth weight lambs (N), those categorised as fetal growth restricted (FGR, 30% lighter at birth) subsequently showed increased fractional growth but remained lighter at necropsy (77d postnatal). Moreover, gender was the dominant influence on size and body composition with females (F) lighter and fatter than males (M). 1 We investigated epigenetic changes underlying this early postnatal phenotype by quantification of methylation at cytosine: guanine (CpG) dinucleotides. Methods: Hepatic DNA and RNA were extracted from FGR (8M, 9F) and N (12M, 9F) offspring. PCR was performed using primers targeting CpG islands of somatotrophic axis genes: insulin, growth hormone ( GH ), insulin-like growth factor ( IGF ) 1, IGF2, H19, insulin receptor (R), GHR, IGFR1, IGFR2 . Using pyrosequencing, methylation status was determined by quantifying cystosine:thymine ratios at 50 CpG sites. mRNA expression of IGF system genes and plasma IGF1/insulin were determined. Results: DNA methylation was wholly independent of prenatal growth status but sexual dimorphism in IGF1 methylation was evident (M < F, 85.3 ± 0.22 vs. 86.2 ± 0.14%, p = 0.008). Correspondingly, IGF1 mRNA:18S and plasma IGF1 were higher in males than in females (23.9 ± 1.48 vs. 11.4 ± 0.49, and 77 ± 3.9 vs. 49 ± 2.3 ng/ml, p < 0.001, respectively). IGF1 methylation was negatively correlated with IGF1 mRNA expression (r = –0.507, p = 0.002), while IGF1 mRNA was positively related to plasma IGF1 (r = 0.884, P < 0.001). Conclusion: FGR did not impact the methylation of growth axis genes but gender differences in early body composition reflect sexual dimorphism in hepatic DNA methylation, IGF1 mRNA expression and plasma IGF1 concentrations.